Macroeconomic Effect on Capital Structure of Chemical Farma Companies - Euis Bandawaty; Nugraha Nugraha; Disman Disman; Maya Sari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Capital structure is a study that has developed a lot since 1958; the development of this study is to examine the influence of micro and macroeconomics on the company's capital structure. Previous studies in Indonesia confirmed that macroeconomics does not affect capital structure. The situation is different empirically. When the covid-19 pandemic occurs, drug companies experience a significant increase. On this basis, researchers seek to examine the effect of macroeconomics on pharmaceutical companies. This research uses a qualitative approach with a sample of PT. Kimia Farma during the period 2016-2020 using multiple regression analysis. The results showed that inflation and interest rates did not affect capital structure. This confirms that macroeconomics does not influence the company's capital structure under normal or abnormal situations.